Aspects of the foraging behaviour of the Antarctic Tern Sterna vittata gaini at Harmony Point, South Shetland Islands - Casaux, Ricardo Jorge; Baroni, A.; Ramón, A.; Favero, Marco; Silva, Paola Valeria (Polar Biology)
During January and February of 2002 and 2003, we studied the diet of the Antarctic Tern Sterna vittata gaini at two colonies in Nelson Island, South Shetland Islands, by identifying the prey fed to chicks by breeders. The fish Notothenia coriiceps was the main prey in both seasons, followed by the myctophid Electrona antarctica, Antarctic krill Euphausia superba and gammarid amphipods. The contribution of fish to the diet increased as chicks grew older. Fish and amphipods were brought to chicks during the day, whereas adults brought Antarctic krill at sunrise and sunset. Both the duration of the feeding trips and the number of trips per foraging bout varied according to the type of prey caught. Preliminary information suggests that, among other causes, the foraging strategy is strongly influenced by the predation pressure of skuas on chicks. Results are compared with the only two previous study on the diet of the Antarctic Tern at the South Shetland Islands.Sterna vittata gaini at two colonies in Nelson Island, South Shetland Islands, by identifying the prey fed to chicks by breeders. The fish Notothenia coriiceps was the main prey in both seasons, followed by the myctophid Electrona antarctica, Antarctic krill Euphausia superba and gammarid amphipods. The contribution of fish to the diet increased as chicks grew older. Fish and amphipods were brought to chicks during the day, whereas adults brought Antarctic krill at sunrise and sunset. Both the duration of the feeding trips and the number of trips per foraging bout varied according to the type of prey caught. Preliminary information suggests that, among other causes, the foraging strategy is strongly influenced by the predation pressure of skuas on chicks. Results are compared with the only two previous study on the diet of the Antarctic Tern at the South Shetland Islands. Fil: Casaux, Ricardo Jorge. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina. Ministerio de Relaciones Exteriores, Comercio Interno y Culto. Dirección Nacional del ...